2023
DOI: 10.1021/acs.cgd.3c00135
|View full text |Cite
|
Sign up to set email alerts
|

Two Proton Conductive Coordination Polymers Constructed by an Unprecedented Structural Transformation of a Phosphine-Based Tricarboxylate Ligand

Abstract: The phosphine-based tricarboxylate 2-(3,3′-dioxo-1λ5-1,1′-(3H,3′H)-spirobi[2,1-benzoxaphosphol]-1-yl)benzoic acid (L) has been intensely studied due to its unique configuration and readily oxidizable phosphorus center. However, the coordination of L with metals have been largely ignored in the field of coordination polymers (CPs). Herein, we report two CPs, [Zn3(L1)2(dib)2(H2O)]·9H2O (1) and [Cu3(L2)2(dib)2]·3H2O (2) (H3L1 = tris(2-carboxyphenyl)phosphine oxide, H3L2 = 2,2′-phosphinico-dibenzoic acid, dib = 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…In recent years, the development of multifunctional luminescent MOFs that combine fluorescence with other properties such as proton conductivity and magnetism has become an intriguing research topic. Introducing two or more functional units into a single-phase material enables multifunctional expression and expands the range of material applications. Proton-conductive materials hold potential for use as solid-state electrolytes in clean and renewable proton exchange membrane fuel cells. , MOFs with highly tunable crystal structures and various modified pore surfaces offer significant opportunities for improving proton conduction and providing ideal crystal models to deepen our understanding of proton transfer mechanisms. , In most cases, proton transport occurs through proton hopping within a hydrogen-bond network. , Gao’s team successfully obtained a luminescent Zr-MOF with proton conductivity through molecular design and investigated the synergistic effect of pH changes and proton conductivity . Zuo et al reported a two-dimensional In­(II)-based conductive MOF with an impressive proton conductivity of up to 1.30 × 10 –2 S·cm –1 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the development of multifunctional luminescent MOFs that combine fluorescence with other properties such as proton conductivity and magnetism has become an intriguing research topic. Introducing two or more functional units into a single-phase material enables multifunctional expression and expands the range of material applications. Proton-conductive materials hold potential for use as solid-state electrolytes in clean and renewable proton exchange membrane fuel cells. , MOFs with highly tunable crystal structures and various modified pore surfaces offer significant opportunities for improving proton conduction and providing ideal crystal models to deepen our understanding of proton transfer mechanisms. , In most cases, proton transport occurs through proton hopping within a hydrogen-bond network. , Gao’s team successfully obtained a luminescent Zr-MOF with proton conductivity through molecular design and investigated the synergistic effect of pH changes and proton conductivity . Zuo et al reported a two-dimensional In­(II)-based conductive MOF with an impressive proton conductivity of up to 1.30 × 10 –2 S·cm –1 .…”
Section: Introductionmentioning
confidence: 99%